STRATEGI GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA DI SEKOLAH DASAR DALAM DAN LUAR NEGERI - Elmalia Futri; Wina Mustikaati; Hisny Fajrussalam (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Motivation is an important factor in elementary school students’ learning outcomes and academic achievement. This qualitative study examined the strategies used by teachers at Sekolah Indonesia Johor Bahru and SDN 5 Sindangkasih Purwakarta. The research aims to explore and compare these strategies, seeking insight into effective practices that can develop a conducive learning environment. The research methods used include interviews, observation, documentation study and triangulation. Data analysis shows that teachers' strategies to increase students' motivation to learn are highly planned and depend on individual teachers' skills. These strategies include interactive teaching methods and creating a supportive classroom atmosphere. The findings show that proper implementation of teachers' strategies can increase students' passion, curiosity, confidence, concentration and ability to be independent in doing tasks. The comparison between Sekolah Indonesia Johor and SDN 5 Sindangkasih Purwakarta is in the different resources and backgrounds of the students. However, there are also many similarities in the commitment to design meaningful and effective learning to increase students' motivation to learn. This research illustrates that effective teacher strategies can increase students' learning motivation. Keywords: teacher skills, qualitative, student learning motivation, teacher strategy